On the origin of transcrystalline morphology in polymers and their composites: Re-evaluation of different views. (June 2015) - Raimo, Maria
Abstract: Morphology of solids is an important subject in materials science since different structures and shapes may determine a variety of mechanical behaviors even for a unique material. The identification of the origin of particular morphology is essential not only for industrial needs as to design materials with tailored properties and to control their response, but also to discover new applications and technologies that otherwise would remain undisclosed. Although the heat flow pattern during solidification is the main factor controlling morphology and, consequently, properties of materials, the correlation between the heat flow and the morphology is often hardly recognized for polymers, preventing the opportunity to benefit from particular thermal effects occurring during crystallization. Indeed, notwithstanding a slow heat flow in polymers opposes the formation of thermal gradients, the very low thermal conductivity of polymer matrices in composites can instead enlarge thermal effects negligible in materials with high thermal diffusivity and low heat capacity as metals.